Clinical Value of the Lactate/Albumin Ratio and Lactate/Albumin Ratio × Age Score in the Assessment of Prognosis in Patients With Sepsis - Chen, Xiaonan; Zhou, Xinjian; Zhao, Hui; Wang, Yanxue; Pan, Hong; Ma, Ke; Xia, Zhijie (Frontiers in Medicine, 2021)
Objective To examine the clinical significance of the blood lactate (Lac)/serum albumin (Alb) ratio and the Lac/Alb × age score for assessing the severity and prognosis of patients with sepsis. Methods A total of 8,029 patients with sepsis, aged > 18 years were enrolled from the latest version of the Medical Information Mart for Intensive Care III (MIMIC-III v.1.4). The general data of the patients were obtained from hospital records. The patients were graded and scored according to their age and then divided into a survival or death group based on their prognosis. The Lac/Alb ratio after ICU admission was calculated and compared between the two groups. The risk factors for death in patients with sepsis were determined using multivariate logistic regression analysis, while mortality was examined using receiver operating characteristic (ROC) curve and survival curve plots. Finally, the values of the Lac/Alb ratio and Lac/Alb × age score for assessing prognosis of patients with sepsis were analyzed and compared. Results The mean age, BMI, SOFA and SAPS II scores were higher in the death group than those in the survival group. The patients in the death group were divided further into four subgroups according to the quartile of the Lac/Alb ratio. Patients with a higher Lac/Alb ratio had a worse prognosis. Age ≥60 years, overweight (BMI≥24 kg/m2), Lac/Alb ratio ≥0.16, SOFA score≥2 points and SAPS II ≥40 points were independent risk factors for death in patients with septic shock. ROC curve analysis indicated that the Lac/Alb ratio, Lac/Alb × age score, and SOFA and SAPS II scores were the best predictors of death in patients with sepsis. The Lac/Alb × age score was characterized by its simple acquisition and ability to quickly analyze the prognosis of patients. Conclusion 1)A high Lac/Alb ratio is an independent risk factor for death in patients with sepsis. 2) Although the prognosis of sepsis can be accurately and comprehensively assessed by multi-dimensional analysis covering multiple indices, the Lac/Alb × age score is more accurate and convenient for providing a general assessment of prognosis, so is worthy of further clinical recognition.